Pengaruh Literasi Al-Qur’an terhadap Sikap Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMA negeri 2 Plus Panyabungan - Gabe Rasoki (PT. Willy Print Art, 2025)
This study aims to analyze the influence of Al-Qur'an Literacy on student learning attitudes in Islamic Religious Education subjects at SMA Negeri 2 Plus Panyabungan. This research uses a quantitative approach with a survey method. The research subjects consisted of 30 students who were all sampled. Data collection techniques were carried out through documentation of student learning outcomes, while data analysis used descriptive statistics and one-sample t-test to compare the average score of student learning outcomes with the Minimum Completeness Criteria (KKM) set by the school. The results showed that the average score (mean) of student learning outcomes was 91.13, which is in the very good category and significantly exceeds the KKM of 70. All students who were sampled achieved learning completeness with a completeness percentage of 100%. The results of the one-sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the average score of student learning outcomes and KKM. This finding indicates that student learning outcomes are not coincidental, but rather statistically meaningful results. The results of this study indicate that the application of Al-Qur'an literacy has a positive impact on the process and student learning outcomes. This approach is able to encourage students to be more active, have a positive learning attitude, and understand Islamic Religious Education material more deeply and contextually.